Fiber degradation and carbohydrate production by combined biological and chemical/physicochemical pretreatment methods of lignocellulosic biomass – A review. (July 2021) - Meenakshisundaram, S.; Fayeulle, A.; Leonard, E.; Ceballos, C.; Pauss, A.
Highlights: Pretreatment is an essential step for the breakdown of lignocellulosic biomass. Combining pretreatment helps to lower the severity of the drawbacks of a single step. Biological-chemical/physicochemical combined pretreatment strategies were reviewed. The order of pretreatment in the combined studies affects the overall efficiency. Abstract: Sustainable biorefinery concepts based on lignocellulosic biomass are gaining worldwide research interest because of their inexpensiveness and abundance. The recalcitrance of lignocellulosic biomass poses a major hindrance to enhance biofuel production. Therefore, a pretreatment step is critical to prepare the substrates for the downstream process. Combining pretreatment steps help to lower the severity of the drawbacks of a single pretreatment step. This paper systematically reviews the combined biological and chemical/physicochemical pretreatment based on fiber degradation and sugar yield. An energy-efficient biological pretreatment method combined with a chemical pretreatment that accelerates the pretreatment times has been seen to be efficient for fiber degradation and sugar yields. However, fungal species, culture conditions, biomass type, the severity of chemical pretreatment and the order of sequential pretreatment influences the relative component contents and sugar yield. Even the same biomass from different sources undergoing similar pretreatment conditions could result in a varying amount of digestibility.